“Shared care planning” and the personalization of clinical paths (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
This paper deals with the relationship between practices of shared care planning (SCP), the Italian way for Advance Care Planning (ACP), and the need for personalization of pathways, as emerging both in care practice and in regulatory developments. The authors discuss the legal tools of Law No. 219/2017 and the broader publicist regulatory context on service integration and personalization of care starting from some clinical scenarios. Legal tools are critically evaluated against the socio-economic models of social and health services. The proposed thesis is that it is necessary to reinterpret services and rights related to “essential levels of care” with communicative and organizational solutions facilitating effectiveness in care relationships. In this sense, the “methodological arch” is presented as an essential tool of professional action to better shape care pathways by enhancing professional and non-professional inputs.
Keywords: Advance care planning; shared care planning; Italian law n. 217/2019; personalization of clinical paths; essential levels of care (L.E.A.); methodological arch